Wear resistance of structural steels carbonitrated by the separate method - Stechyshyn, M.S.; Dykha, O.V.; Zdorenko, D.V.; Oleksandrenko, E.G. (Problems of Tribology, 2025)
The article investigates the influence of technological modes of separate carbonitriding of carbon steels on the thickness and microhardness of the hardened layer. Two hardening variants were investigated: first, carburizing of surfaces was carried out in argon-propane, and then nitriding in argon-nitrogen mixtures and vice versa. As the conducted studies have shown, the variant of the hardening technological process significantly affects the physical and mechanical characteristics of the hardened layer. In all two variants of the technological process, the hardened layer consists of a surface carbonitride zone and a diffusion zone of internal nitriding, but the properties of these zones are different in different variants of the technological process. Thus, when hardening steels according to the first mode, the thickness of the carbonitride zone is maximum, and the internal nitriding zone has a small thickness. This is explained by the fact that the carbonitride layer created on the steel surface at the first stage of processing performs the function of shielding the surface from the penetration of nitrogen ions into the surface layer of the metal. When hardening according to the second mode, the carbonitride zone has a slightly smaller thickness, but a more developed internal nitriding zone.